Evaluation of the effectiveness of mustard (Brássica júncea) as a CO2 sequestering agent at elevated temperatures - Kuryntseva Polina; Galieva Gulnaz; Sultanova Lola; Pronovich Natalia (BIO Web of Conferences)
Preservation and increase of soil fertility is one of the main tasks of modern agriculture. The use of siderates is one of the technologies of ecologization of agriculture. In the framework of this study we evaluated the possibility of using mustard (Brássica júncea) as a CO2 trap in conditions of elevated temperatures. It was shown that with increasing temperature from 20 to 30°C there is an increase in carbon fixation in the phytomass of plants. The maximum carbon fixation in mustard (B. júncea) phytomass was established at a temperature of 30 C and amounted to 439.5 kgC/ha.